(untitled) (Health Renaissance, 2012)
Introduction: Passage of meconium in utero is a dangerous sign for fetal outcome which influence the decision to deliver as well as the mode of delivery. Methods: This descriptive case control study was carried out in the department of Obstetrics and Gynaecology, Koshi Zonal Hospital from March 2006 to July 2006. A total of 50 women with meconium stained amniotic fluid( MSAF) were studied to identify maternal and fetal outcome and was compared with women with clear amniotic fluid. Results: Normal delivery was significantly higher (58%) in clear liquor group as compared to MSAF group (22%). Cesarean section was more common in MSAF group (66%) where as it was (38%) in the clear liquor group (p=0.005). Low Apgar scores of < 5 at one minute was seen in 48% of MSAF and 6% of clear liquor born babies (p<0.2). But at 5 minutes low Apgar score persisted in same 48% of MSAF babies whereas it was seen in 12% of clear liquor group (p<0.000). Among the babies born with MSAF 34% were referred to higher center compared to 6% in clear liquor babies (p=0.000). Four babies with thick MSAF and one baby with clear liquor had neonatal death (p=0.005). Conclusion: Mode of delivery and fetal outcome were adversely affected by the presence of thick meconium stained liquor as compared to clear liquor. Additional monitoring facilities e.g. cardiotocography (CTG) if available would reduce fetal distress and allow timely intervention in such cases. DOI: http://dx.doi.org/10.3126/hren.v10i3.7135 Health Renaissance; September-December 2012; Vol 10 (No.3);198-202